UJI COBA ARANG SEKAM PADI SEBAGAI MEDIA FILTRASI DALAM MENURUNKAN KADAR Fe PADA AIR SUMUR BOR DI ASRAMA JURUSAN KESEHATAN LINGKUNGAN MANADO - Jasman Jasman (POLTEKKES KEMENKES MANADO, 2011)
Water is a chemical compound that is essential for the life of mankind and other living being sand their function as life will not be replaced by other compounds. Filtration is a process of water treatment by means of raw water flowing through a filter with media from granular materials with a certain grain diameter and arranged with a certain thickness. This type of research is experimental, with the aim to determine whether there is decreased levels of Febyrice huskcharcoal filtration at the water wells drilled in Environmental Health Dormitory Manado. Filtration arrangement made with gravel, palm fiber and rice huskcharcoal. Data obtained from the research results processed by using statistical test student